Implementation of the Nadhliyah Method in Enhancing Children's Spiritual Intelligence at Quran Memorization Center At-Taqwa Binjai - Dira Wulandari; Hadinata, Arie Bastian (The Islamic Education and Multiculturalism Foundation, 2025)
AbstrakSpiritual merupakan aspek penting dalam tumbuh kembang anak yang dapat dibentuk melalui pembelajaran tahfidz Al-Qur'an dengan metode yang tepat. Penelitian ini bertujuan untuk menganalisis penerapan metode An Nadhliyah dalam meningkatkan kecerdasan spiritual anak di Rumah Tahfidz At Taqwa Binjai. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Data dikumpulkan melalui observasi, wawancara, dan tes hafalan, kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa metode An Nadhliyah efektif dalam meningkatkan kemampuan menghafal Al-Qur'an dan mengembangkan kecerdasan spiritual anak melalui pendekatan komprehensif dan terpadu. Faktor pendukung keberhasilan metode ini antara lain keterlibatan aktif guru dan orang tua, lingkungan belajar yang kondusif, serta strategi mengajar yang bervariasi. Namun, kendala yang dihadapi antara lain perbedaan kemampuan menghafal dan konsistensi penerapan metode di luar kelas. Dengan demikian, metode An Nadhliyah dapat menjadi alternatif yang efektif dalam mengembangkan kecerdasan spiritual anak melalui pembelajaran tahfidz yang aplikatif dan bermakna. Implikasi dari penelitian ini adalah metode ini dapat diterapkan secara lebih luas dengan dukungan sistem pembelajaran yang berkelanjutan dan keterlibatan aktif berbagai pihak.Kata Kunci: Metode Al-Qur'an; Kecerdasan Spiritual; Metode An Nadhliyah; Pembelajaran Anak; Penelitian Tindakan Kelas AbstractSpiritual intelligence is an important aspect of child development that can be formed through learning tahfidz Al-Qur'an with the right method. This study aims to analyze the implementation of the An Nadhliyah method in improving children's spiritual intelligence at Rumah Tahfidz At Taqwa Binjai. This research uses the Classroom Action Research (PTK) method with the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and memorization tests and then analyzed descriptively. The results showed that the An Nadhliyah method is effective in improving the ability to memorize the Qur'an and developing children's spiritual intelligence through a comprehensive and integrated approach. Supporting factors for the success of this method include the active involvement of teachers and parents, a conducive learning environment, and varied teaching strategies. However, challenges faced include differences in memorization ability and consistency in the application of the method outside the classroom. In conclusion, the An Nadhliyah method can be an effective alternative in developing children's spiritual intelligence through applicable and meaningful tahfidz learning. The implications of this study suggest that this method can be applied more widely with the support of a sustainable learning system and the active involvement of various parties. By fostering collaboration among educators, parents, and community members, the An Nadhliyah method can create a holistic learning experience that nurtures spiritual growth. Ultimately, this approach not only enhances memorization skills but also instills a deeper understanding of the material, encouraging students to engage more fully with their faith and values.Keywords: Qur'anic Method, Spiritual Intelligence, An Nadhliyah Method, Children's Learning, Classroom Action Research